THE EFFECTS OF BOTULINUM TOXIN IN MYOFASCIAL PAIN MODULATION: NEW PERSPECTIVES FOR ESTHETIC AND FUNCTIONAL DENTISTRY - Santiago, Anna Laira Malaquias (Revista Sistemática, 2022)
Botulinum toxin (BoNT) has become an increasingly valuable tool in dentistry, extending beyond cosmetic applications to therapeutic interventions in myofascial pain modulation. Myofascial pain syndrome, often associated with temporomandibular disorders and parafunctional habits, presents a clinical challenge due to its multifactorial etiology and frequent resistance to conventional therapies. By blocking acetylcholine release at the neuromuscular junction and interfering with pain-related neuropeptides, BoNT provides both muscle relaxation and analgesic effects. Clinical studies have reported reductions in pain intensity, functional improvement, and enhanced quality of life for patients with orofacial myofascial pain following BoNT treatment. Additionally, its esthetic benefits, such as improved facial harmony and reduction of masseter hypertrophy, align with modern dentistry’s emphasis on holistic, patient-centered care. Despite concerns about the temporary nature of its effects, repeated applications, and the need for standardized protocols, the evidence suggests BoNT represents a safe and effective adjunctive or alternative therapy. Future research should continue to refine clinical guidelines and evaluate long-term outcomes, consolidating BoNT’s role as a therapeutic and esthetic agent in contemporary dental practice.